(untitled) (Eurasian Medical Research Periodical, 2023)
During pregnancy, the fetus develops in a sterile environment because the placenta and fetal membranes act as a barrier to bacterial infection throughout gestation. Rupture of the fetal bladder is a serious condition fraught with a number of maternal and fetal complications, and as the waterless interval lengthens, regardless of the cause of the ruptured membranes, the risk of intrauterine infection increases [4]. Chorioamnionitis (CA) is an acute inflammation of the placental membranes and chorion, usually due to an ascending polymicrobial bacterial infection in a ruptured membrane. Chorioamnionitis can occur with intact membranes, and this, occurs with genital mycoplasmas (Ureaplasma urealiticum and Mycoplasma hominis), found in the lower genital tract in over 70% of women